CUSTOMER SATISFACTION OF SELECTED BRANCHES OF BANK OF CEYLON IN BATTICALOA DISTRICT - Ismail, M.B.M. (University of Jaffna, 2016)
Studies have also found that different studies have found different factors for customer satisfaction. But, these studies were carried out in different organsational settings such as service industries. This study is conducted in two selected bank branches of Bank of Ceylon in Batticaloa District. This study attempts to know about factors and factor rankings for customer satisfaction. Sample size considered in this study is 100 customers. These customers were contacted during the banking hours while they finish their banking activities without disturbing them and banking business. Results of the reliability revealed that items are higher reliable (0.700). Since value of Kaiser-Meyer-Olkin is 0.519 which reveals a satisfactory value. Bartlett's Test of Sphericity which is measured by approximate chi square. Value of significant approximate chi- square is 1637.840 with 231 degrees of freedom. Initial and extracted communalities for factors are 1 and greater than 0.6. Total eigenvalues that are greater than 1 is selected. There are 8 factor components that explain around 81% of variation towards customer satisfaction. It is concluded that, on the basis of the factor score, factors can be ranked.
Keywords: Customer; Satisfaction.